ANALISA TINGKAT KREDIT MACET PADA BANK BPR PERMATA HATI JAYA DI SAMARINDA PERIODE 2015-2017 - camelia Verahastuti3, HELDA ARIANI Imam Nazarudin Latif2 (EKONOMIA, 2021)
The purpose of this study was to determine and analyze the level of bad credit at the Permata Jaya Credit Bank Samarinda using the Non Performing Loan (NPL) ratio.The theory used in this research is financial management and Non-Performing Loans (NPL). Data collection technique used is field research in which activities are interviewing company leaders and library research which takes financial statement information and studies related theories.This research was conducted on the financial statements of PT. BPR Permata Hati Jaya Samarinda in the period 2015 to 2017. The analytical tool used in this study is the Non Performing Loan (NPL) ratio.The results of the study stated that in 2015 the ratio (NPL) was 1.35% and was categorized as very healthy, then dropped by 0.49% and 0.45% in 2016 and 2017 and categorized as very healthy. The decrease in Non-Performing Loans (NPLs) was due to improvements in credit quality in each sector. Non Perfoming Loan (NPL) in 2015, 2016 and 2017 can be categorized as very healthy because according to the standards of Bank Indonesia the percentage of Non Performing Loan (NPL) at PT. BPR Permata Hati Jaya Samarinda is below 5%.